Identitas nasional dalam algoritma: Transformasi gotong royong menjadi gerakan digital kaum muda Indonesia - iqbal, muhammad (Maliki Interdisciplinary Journal, 2025)
The digital era has transformed Indonesia’s sociocultural landscape, particularly in how young generations express the nation’s noble values. This research examines the transformation of gotong royong (mutual cooperation) practices from traditional forms into digital movements initiated by Indonesian youth. Through analysis of digital gotong royong platforms such as Bagirata, the study finds that Indonesian collectivist values have not diminished due to digitalization but have undergone adaptive meaning reconstruction. The Bagirata platform successfully raised over 500 million rupiah for 1,475 pandemic-affected workers, demonstrating the effectiveness of digital gotong royong. Indonesian youth prove their capability as bridges between cultural heritage and technological innovation, utilizing algorithms to strengthen social cohesion. Unlike individualistic global crowdfunding models, Indonesia’s digital gotong royong is grounded in inclusive distributive justice principles. This research concludes that digital transformation can strengthen national identity when designed in alignment with humanitarian values. Synergy between educational institutions, government, and society is needed to ensure digital technology remains an empowerment instrument that preserves Indonesian local wisdom.